Development of 3D Web-Based Science Learning Media Assisted by Qr Codes on Solar System Material (Indo-MathEdu Intellectuals Journal, 2025)
One of the technological innovations that can be used is WEB 3D-based learning media, which combines visual elements and text in a more real way. The following research intends to develop a WEB-Based 3D Learning Media equipped with a QR Code as a support for Solar System materials for grade VII junior high school students. This media is designed to be valid, practical, and effective in improving student understanding. The research method used is Research and Development (R&D) with a 4-D development model approach, which includes four main stages: define, design, develop, and disseminate. The research instruments include validation questionnaires, practicality questionnaires, and effectiveness questionnaires. The data obtained were analyzed using the Likert scale and the Guttman scale to assess the level of validity, practicality, and effectiveness of the developed learning media. The results of the 3D media validity test obtained a very valid category with an average score of 85%. The results of the practical test on the use of 3D media from teachers and students are in the very practical category with a teacher response questionnaire score of 93% and student responses of 94%. The effectiveness of the use of 3D media on students' learning interests is very effective with a student response questionnaire score of 91%. Thus, the following research has produced a WEB-based 3D science learning media on Solar System material for grade VII junior high school that is valid, practical, effective and ready to be disseminated.